Comparing Technology-Based Reading Intervention Programs in Rural Settings. (May 2022) - Stein, Brit'ny; Solomon, Benjamin G.; Kitterman, Chase; Enos, Debbie; Banks, Elizabeth; Villanueva, Sierra
An ever-growing call for the use of evidence-based practice has come up against the logistical hurdles of a lack of resources and expertise, particularly in rural schools that work with historically underserved students. Although integrated learning systems (ILSs)—stable and likely requiring fewer resources than personnel—do not offer a complete solution to this problem, they may serve as a useful resource, particularly for milder literacy deficits. And yet, there is a surprising lack of empirical research on their effectiveness, particularly for contemporary programs. This study examines the effectiveness and efficiency of two popular ILSs, Lexia and iStation, both of which use a blended model of computer and traditionally delivered instruction, and compares them against business-as-usual (BAU) conditions across a variety of outcomes. Results suggest both programs resulted in meaningful growth across an academic year of implementation, although generally no more so than that observed in the BAU condition. However, Lexia yielded the highest level of instructional efficiency. That is, despite comparable growth across conditions, Lexia required less staff time to implement per student participant.